PEMERIKSAAN FAKTOR-FAKTOR YANG MEMPENGARUHI PASAR KERJA DAN ALASAN DI BALIK KEPUTUSAN SISWA AKUNTANSI MENJADI AKUNTAN PUBLIK. - Tipa, Handra; E Janrosl, Viola Syukrina; Arista, Anggia; Yuliadi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
The decision of accounting students to pursue a career in accounting is heavily influenced by factors related to the job market. Public accounting is a popular career choice for accounting students, but job market factors can have a big impact. A career as a public accountant is typically more appealing to accounting students who possess the necessary skills and have a keen interest in accounting and finance. The decision of accounting students to pursue a profession as public accountants is heavily influenced by their strong sense of motivation. Factors such as financial attractiveness, professional responsibility, interest in the accounting sector, and environmental influences can serve as sources of motivation. A job as a public accountant would typically require more dedication and accomplishment from those who possess high motivation. Research on the simultaneous impact of motivation and job market conditions has a big bearing on whether someone decides to become a public accountant and is useful in understanding what makes people want to become public accountants